2020
DOI: 10.1126/sciadv.aay8301
|View full text |Cite
|
Sign up to set email alerts
|

How the effects of actions become our own

Abstract: Every day, we do things that cause effects in the outside world with little doubt about who caused what. To some, this sense of agency derives from a post hoc reconstruction of a likely causal relationship between an event and our preceding movements; others propose that the sense of agency originates from prospective comparisons of motor programs and their effects. Using functional magnetic resonance imaging, we found that the sense of agency is associated with a brain network including the pre–supplementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…fMRI scans were performed during the execution of a temporal-judgement task (see Fig. 1 , see also Zapparoli et al , 2020 ). There were active and passive conditions.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…fMRI scans were performed during the execution of a temporal-judgement task (see Fig. 1 , see also Zapparoli et al , 2020 ). There were active and passive conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The sense of agency has recently been associated with the planning premotor phase of action generation ( Kühn et al , 2013 ; Zapparoli et al , 2020 ; Seghezzi and Zapparoli, 2020 ). It has been suggested that the arising of the sense of agency may be contingent on the generation of a forward model, a mechanism whereby we estimate the next motor state and the sensory consequences of any planned movement (see Kim et al , 2019 for a discussion of these concepts in the context of GTS).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations